Polarization digital holographic microscope for live cell imaging - Singh R.K.; Chaubey S.K.; Rathor M.; Tamang R.; Koch B. (My University, 2025)
Polarization, a fundamental feature of the light, is a useful parameter in understanding the complex optical responses of the system and to unravel unique properties that are otherwise missing. Usually, measurement of the polarization demands multiple measurements, which is not appropriate for live imaging. In this paper, we discuss and present some of our recent works on development of polarization digital holographic microscope for spatially resolved and a label-free imaging. Our emphasis is on single-shot polarization imaging and its possible applications in live cancer cell imaging. © 2024 SPIE.